Achieving a more informed understanding of sexual abuse through working with perpetrators, as well as survivors - Wilcox, Daniel T. (Sexual crime, 2024)
In this chapter, the authors explore the relationship dynamic that exists between perpetrators, survivors, and therapist. It describes key requirements for formulating more effective interventions, with a need for attuned, informed and open style of engagement, as well as knowledge of the experience of both the abuser and the survivor. Strategies for enhancing the development of more meaningful therapeutic relationships are explored, as well as barriers to progress and ongoing efforts to protect potential future victims. A range of case examples are explored, principally focusing on sexual harm, though describing links with emotional and physical abuse, in particular around domestic violence. Attention is directed to ways of effectively engaging with perpetrators, such that they can take up more responsible and constructive roles in society.